Planning and accounting activities and periodic reporting of the prosecutor's office of the Kabardino-Balkarian autonomous region in 1925-1926: features and prospects of source analysis - Zalim T. Mirzoev (Кавказология)
The article is devoted to the peculiarities and prospects of the source analysis of planning and accounting activities and periodic reporting of the Prosecutor's office of the Kabardino-Balkarian Autonomous Region in 1925-1926. For this purpose, the plans of regional and district prosecutor's offices, checklists for collecting information on the current activities of regional prosecutor's offices, notebooks for recording the participation of public prosecutors in court sessions, statements on the movement of inquiries, investigative cases, cases of press revelations, monthly statements, survey reports, characteristics, literary (text) and "digital" (quantitative) reports (with elements of statistical generalization), summary reports on personnel and current activities, semi-annual reports on the work of the Prosecutor's office of the KBAO and district prosecutor's offices, crime reports, etc. It was established that information on the personnel composition, plans and accounting of daily work, the management of assistants, the organization of the activities of prosecutors, the effectiveness of work with the rural population, the quality of supervisory activities, the state of crime, interaction with court authorities, criminal labor institutions, preventive activities to combat crime were subject to accounting etc. It is assumed that the analysis of the planning, accounting and reporting documentation of the Prosecutor's office of the KBAO in the second half of the 20s of the twentieth century has a further research perspective for studying the features of the formation and development of the mechanism of the young Soviet state and its system of law enforcement agencies, the dynamics of the cadre and the regional specifics of supervisory activities for compliance socialist legality in the territory of the KBAO and the fight against crime, etc.